2023
DOI: 10.3897/bdj.11.e97484
|View full text |Cite
|
Sign up to set email alerts
|

The InBIO barcoding initiative database: DNA barcodes of Iberian Trichoptera, documenting biodiversity for freshwater biomonitoring in a Mediterranean hotspot

Abstract: The Trichoptera are an important component of freshwater ecosystems. In the Iberian Peninsula, 380 taxa of caddisflies are known, with nearly 1/3 of the total species being endemic in the region. A reference collection of morphologically identified Trichoptera specimens, representing 142 Iberian taxa, was constructed. The InBIO Barcoding Initiative (IBI) Trichoptera 01 dataset contains records of 438 sequenced specimens. The species of this dataset correspond to about 37% of Iberian Trichoptera species diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In addition, the genetic analyses agree with the morphological characteristics, corroborating the close phylogenetic relationship of A. taounate with A. braueri, A. cinereus, and A. alentexanus. Although Pauperio et al (2023) concluded that DNA barcodes, based on mtCOI (interspecific uncorrected pairwise distance (p) = 0.411, Table 1), might not differentiate between A. braueri and A. alentexanus, we consider the latter provisionally as a valid species. In the paper originally describing A. alentexanus, Martín et al (2016) cited a paratype from Benamahoma, but we have examined numerous males captured in this locality, and others (see material examined), and have not found any specimen with the characteristics of that latter species.…”
Section: Dna Analysis To Establish the Conspecificity Of Larva And Ad...mentioning
confidence: 78%
“…In addition, the genetic analyses agree with the morphological characteristics, corroborating the close phylogenetic relationship of A. taounate with A. braueri, A. cinereus, and A. alentexanus. Although Pauperio et al (2023) concluded that DNA barcodes, based on mtCOI (interspecific uncorrected pairwise distance (p) = 0.411, Table 1), might not differentiate between A. braueri and A. alentexanus, we consider the latter provisionally as a valid species. In the paper originally describing A. alentexanus, Martín et al (2016) cited a paratype from Benamahoma, but we have examined numerous males captured in this locality, and others (see material examined), and have not found any specimen with the characteristics of that latter species.…”
Section: Dna Analysis To Establish the Conspecificity Of Larva And Ad...mentioning
confidence: 78%
“…OTUs were then compared to online databases (BOLD and NCBI) and identified to the lowest taxonomic rank possible, taking into account the likelihood of occurrence in Portugal and Iberia in the case of arthropods, and in the study area in the case of plants. Strong efforts have been made to generate barcode libraries of insects in the region (e.g., Ferreira et al., 2020; Pauperio et al., 2023; Sousa et al., 2021), thereby reducing the likelihood of erroneous assignments. Whenever an OTU matched several species, genus or families at similar identity levels, we selected the most inclusive taxonomic rank.…”
Section: Methodsmentioning
confidence: 99%
“…with high co-occurrence levels (>95% of samples). This greatly re- (e.g., Ferreira et al, 2020;Pauperio et al, 2023;Sousa et al, 2021), thereby reducing the likelihood of erroneous assignments. Whenever an OTU matched several species, genus or families at similar identity levels, we selected the most inclusive taxonomic rank.…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…The InBIO Barcoding Initiative (IBI) makes use of High-Throughput Sequencing technologies to construct a reference collection of morphologically identified Portuguese specimens and respective DNA barcodes (e.g. Rebelo et al 2020 , Ferreira et al 2021 , Oliveira et al 2021 , Pauperio et al 2023 , Rosa et al 2023 ). DNA barcoding offers a rapid, cost-effective alternative tool for both the identification of described species and the discovery of new ones ( Hebert et al 2003 , Savolainen et al 2005 , Mitchell 2008 , our papers).…”
Section: Introductionmentioning
confidence: 99%